Wireless communication technology's selection for landslide monitoring in rural area - Mustafa I.S.; Din N.M.; Ismail A.; Redzuwan R.M.; Omar R.C.; Khalid N.H.N. (Institute of Electrical and Electronics Engineers Inc., 2023)
For the past 5 decades, a major number of Tenaga Nasional Berhad (TNB) transmission towers that traversed throughout Peninsular Malaysia have already existed. Some of the tower located at a mountainous terrain and suspected to be insecure and risky. One method is monitoring the landslide in real-time, by deploying various sensor at the high risk area. This paper presents the applicability of multicriteria decision making (MCDM) method, specifically Analytical Hierarchy Process (AHP) to select the wireless communication technology for transmitting the sensor data to the control centre. Criteria that influence the selection are technical, economical, infrastructure and functionality. On the other hand, four alternative options are fiber optical network, cellular, wireless LAN and zigBee. 2013 IEEE.